Enzymatically activated emulsions stabilised by interfacial nanofibre networks. Issue 9 (1st February 2016) - Moreira, Inês P.; Sasselli, Ivan Ramos; Cannon, Daniel A.; Hughes, Meghan; Lamprou, Dimitrios A.; Tuttle, Tell; Ulijn, Rein V.
Abstract : An on-demand emulsifier is presented which is based on dephosphorylation and biocatalytic assembly of an aromatic peptide amphiphile, involving phosphatase triggered conversion of a modest emulsifier into more permanent fibrous networks at the aqueous/organic interface. Abstract : We report on-demand formation of emulsions stabilised by interfacial nanoscale networks. These are formed through biocatalytic dephosphorylation and self-assembly of Fmoc(9-fluorenylmethoxycarbonyl)dipeptide amphiphiles in aqueous/organic mixtures. This is achieved by using alkaline phosphatase which transforms surfactant-like phosphorylated precursors into self-assembling aromatic peptide amphiphiles (Fmoc-tyrosine-leucine, Fmoc-YL) that form nanofibrous networks. In biphasic organic/aqueous systems, these networks form preferentially at the interface thus providing a means of emulsion stabilisation. We demonstrate on-demand emulsification by enzyme addition, even after storage of the biphasic mixture for several weeks. Experimental (Fluorescence, FTIR spectroscopy, fluorescence microscopy, electron microscopy, atomic force microscopy) and computational techniques (atomistic molecular dynamics) are used to characterise the interfacial self-assembly process.